2003
DOI: 10.1108/01437720310479723
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and wage effects of “family‐friendly” fringe benefits

Abstract: Family‐supportive employment benefits have become increasingly popular in recent years as an employer response to the increasing labor force participation of women, and the consequent need to balance work and family life. Economic theory predicts that these types of fringe benefits could at least partially pay for themselves through a combination of increased productivity and lower wages. A survey of 120 employers in an upstate New York county provides data on benefits packages and outcome measures that are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 2 publications
3
86
0
Order By: Relevance
“…The availability of practices may also increase positive job-related attitudes, work effort and contextual behaviours by enhancing social exchange processes; as symbols of organizational concern for employees, work-life practices promote employee interest in and obligation to the organization (Pfeffer, 1981). Providing work-life practices can allow organizations to offer lower wages in exchange (Baughman et al, 2003), and attract investors by signalling the organization's legitimacy (Arthur, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of practices may also increase positive job-related attitudes, work effort and contextual behaviours by enhancing social exchange processes; as symbols of organizational concern for employees, work-life practices promote employee interest in and obligation to the organization (Pfeffer, 1981). Providing work-life practices can allow organizations to offer lower wages in exchange (Baughman et al, 2003), and attract investors by signalling the organization's legitimacy (Arthur, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Baughman (2003) has found that employers tend to decrease wages once several benefits such as medicare, bonus, and annual leave, had been offered to employees after a few years. Woodbury (1983) in his study has found that workers view benefits and wages as substitutes, willing to give up wages for more benefits.…”
Section: The Importance Of Fringe Benefits To Employees' Satisfactionmentioning
confidence: 99%
“…The benefits are not frequently issued towards assessment and are consequently cheaper to achieve during an employer throughout the market [2]. Therefore, cheaper the benefits ought to amplify employee performance.…”
Section: Benefitsmentioning
confidence: 99%
“…Further the benefits can proceed as an alternate for salary. To inspect the employer investigation facts and establish the employee's reduced the salary; once numerous benefits had obtained to the individual after a few years [2]. Moreover, the employees sight the benefits and salary as alternatives, disposed to provide salary in trade for extra benefits.…”
Section: Benefitsmentioning
confidence: 99%